2014
DOI: 10.1111/hpb.12197
|View full text |Cite
|
Sign up to set email alerts
|

Early oral feeding after pancreatoduodenectomy enhances recovery without increasing morbidity

Abstract: The introduction of an early oral feeding strategy after PD reduced the time to resumption of adequate oral intake and length of hospital stay without negatively impacting postoperative morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 29 publications
1
26
0
13
Order By: Relevance
“…A total of 51 articles were utilized for the review, with 14 addressing malnutrition and pancreatic dysfunction at pancreatic cancer diagnosis [13,14,15,16,17,18,19,20,21,22,23,24,25,26]; 19 addressing pancreatic dysfunction after surgery [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45], including 10 which also discussed preoperative dysfunction and nutrition [27,30,31,32,33,35,37,39,40,41]; and 18 addressing nutritional intervention [11,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62] (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 51 articles were utilized for the review, with 14 addressing malnutrition and pancreatic dysfunction at pancreatic cancer diagnosis [13,14,15,16,17,18,19,20,21,22,23,24,25,26]; 19 addressing pancreatic dysfunction after surgery [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45], including 10 which also discussed preoperative dysfunction and nutrition [27,30,31,32,33,35,37,39,40,41]; and 18 addressing nutritional intervention [11,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62] (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Results showed that NJEEN was associated with a significantly higher frequency and severity of postoperative pancreatic fistula (POPF), but did not result in a significant difference in the incidence of postoperative hemorrhage, infection, grade of complications, and length of stay. In contrast, Gerritsen et al found that early oral feeding after PD resulted in a decreased length of hospital stay and no differences in Clavien-Dindo Grade III or higher complications, delayed gastric emptying, postoperative hemorrhage, and mortality when compared to patients who received nasojejunal tube (NJT) feeding [49]. As such, introducing oral feeding earlier than previously estimated may reduce the hospitalization time with minimal secondary drawbacks in patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, dislodgement occurred in 36% of patients, which is comparable with previous studies in patients after pancreatoduodenectomy receiving tube feeding via an endoscopically placed tube. 3,4,9 A potential benefit of the EM-guided technique is that incorrectly placed or dislodged tubes, which are not completely removed, can be repositioned with the EM-guided stylet. This prevents discomfort because the tube does not have to pass the nose and oropharynx again and is less costly because the original tube and stylet can be used.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 These patients will have to undergo postoperative placement of a nasojejunal feeding tube, and up to 27% of these patients will require a second or third procedure because of dislodgement or blockage of the tube. 3,4,9 There are various techniques for nasojejunal feeding tube placement, but they all have their specific disadvantages. Blind placement of feeding tubes beyond the pylorus is frequently unsuccessful and may lead to complications such as pneumothorax and pneumonia due to inadvertent placement in the bronchus.…”
mentioning
confidence: 99%
“…An observational study reported the effects of implementation of early oral feeding as compared to routine enteral feeding through a nasojejunal tube (NJT) [65]. The study found no significant difference in the incidence of POPF between the two types of feeding strategies (12 % vs. 12 %, p=0.999).…”
Section: Postoperative Approaches To Reduce the Rate Of Popfmentioning
confidence: 99%